Forgiveness and Components of I- concept Interconnection Regarding Adolescents Social Correction Groups - Dudkina, Aija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The aim of the research is to clarify the components of the I-concept of the personality that promote maturity to forgive the adolescents in social-correction groups. The research results statistically reveal a meaningful interconnection among forgiveness and the components of the personality I-concept, for instance, the interconnection between the scale of forgiveness and the pesonality’s associations with I-real components, i.e., the submission to peer pressure and dependency components are linked with the emotional responsiveness scale in accordance with the questionnaire about forgiveness; also, the personality concept about the I- ideal components which are friendship and dependency as well as the authoritarian components are linked with the emotional responsiveness scale according to the questionnaire about forgiveness. Assisting adolescents and youth psychologically, the possible assistance should be focused on revealing I-in the Eyes of the Others. The analysis of the results let us judge that the concept of I- ideal differs greatly from I- real; in such cases the individual experiences discomfort and dissatisfaction as well. In the research discrepancies turned up in the personality I-concept; also, I-Ideal content greatly differs from adolescents current, real opportunities which, in their own way, may hinder a personality favourable development as well as do not encourage the development of forgiveness.